Cultivating the Character of Social Care and Tolerance (Case Study of Agro Nuur El-Falah Islamic Boarding School Pulutan Salatiga) - Maslakah, Wijayanti; Sutomo, Imam (CV. Creative Tugu Pena, 2022)
The purpose of this study is to determine the cultivation of the character of social care and tolerance as well as the faced obstacles in inculcating these characters to the students at the Pondok Pesantren Agro Nuur El-Falah Salatiga. This research is a field research using analytical descriptive qualitative method with the variety of case studies. The research data was obtained through observation, interviews, and documentation. The results of this study indicate that; first, the inculcation of the character of social care into students at the Pondok Pesantren Agro Nuur El-Falah through several activities, for instance caring for the environmental cleanliness, visiting the ill friends, sending prayers for students or students' families who died, infaq cross-subsidies, orphanage activities and picket distribution. Second, the cultivation of the character of tolerance into students at the Pondok Pesantren Agro Nuur El-Falah by gathering students from various regions in one room, and maintaining good relations with friends from one area through consulate activities once in a week. Third, the faced obstacles in inculcating the character of social care and tolerance in students when they found students who had never stayed and had to adapt the regulations as the new environment at the Pondok Pesantren Agro Nuur El-Falah Salatiga Keywords: Character Social Care, Character Tolerance, Cultivating Social Character